PENGARUH KOMUNIKASI ORGANISASI TERHADAP KEPUASAN KERJA DOSEN TETAP PTM DI SULSEL - Muh. Tahir (Jurnal Komodifikasi, 2019)
The purpose of this study was conducted with the aim of analyzing the Effect of Organizational Communication on the Job Satisfaction of Permanent Lecturers of Muhammadiyah Universities (PTM) in South Sulawesi. This research uses survey method. This research was conducted on 5 PTM which have the most permanent lecturers from 19 PTM in South Sulawesi with a population of 841 permanent lecturers with a sample determination of 276 respondents using the Slovin formula. Data from the questionnaire were analyzed using SEM Amos 21. The results found that organizational communication has a significant positive effect on job satisfaction.